(untitled) (Itinera, 2013)
The cinematographic detail is a relevant aesthetical component. It can be neither isolated nor explained by the foreground scenery. It is necessary to consider the specific aspects of cinematic details within a wider framework, which includes both incidental and transversal components. The paper shows how filmography directors like Jean-Pierre Jeunet and Wes Anderson clarify a new perspective on this topic.